2015
DOI: 10.4103/0366-6999.147785
|View full text |Cite|
|
Sign up to set email alerts
|

The Survey of Birth Defects Rate Based on Birth Registration System

Abstract: Background:To investigate the surveillance trend of birth defects, incidence, distribution, occurrence regularity, and their relevant factors in Xi’an City in the last 10 years for proposing control measures.Methods:The birth defects monitoring data of infants during perinatal period (28 weeks of gestation to 7 days after birth) were collected from obstetrics departments of all hospitals during 2003–2012. Microsoft Excel 2003 was used for data input, and Statistical Package for the Social Sciences version 16.0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
22
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(24 citation statements)
references
References 12 publications
1
22
0
Order By: Relevance
“…The incidence of MSCs among vaccinated women (6.0%) was similar to that previously reported in vaccinated women aged 15–25 years from the HPV‐023 study (8.1%) , and the incidence of NOCD and NOADs was very low (0.3% and 0.1%, respectively), also in line with previous reports (0.0–3.0% and 0.0–1.0%, respectively) . The incidence of congenital anomalies in offspring of all pregnant women throughout the study was comparable with that observed in the large global clinical trial , and was low compared with the reported incidence of congenital anomalies worldwide and in China .…”
Section: Discussionsupporting
confidence: 89%
“…The incidence of MSCs among vaccinated women (6.0%) was similar to that previously reported in vaccinated women aged 15–25 years from the HPV‐023 study (8.1%) , and the incidence of NOCD and NOADs was very low (0.3% and 0.1%, respectively), also in line with previous reports (0.0–3.0% and 0.0–1.0%, respectively) . The incidence of congenital anomalies in offspring of all pregnant women throughout the study was comparable with that observed in the large global clinical trial , and was low compared with the reported incidence of congenital anomalies worldwide and in China .…”
Section: Discussionsupporting
confidence: 89%
“…4 In China, the incidence of congenital malformations is 5.6%, with ~900,000 new birth defect cases each year. 5 Congenital heart defects (CHDs), which accounted for 27% of all birth defects in China in 2011, are the most common severe congenital anomalies and are the leading causes of infant mortality in China (Report MoHoPsRoCCBDP). A recent report showed a rapid increase in CHDs in China during 1996–2011.…”
Section: Introductionmentioning
confidence: 99%
“…The maximum values are close to those of the municipality of São Paulo (Brazil), which was 160/10,000 LB (32) , but lower than those of the United States (300/10,000 LB in 2006) (33) , Chile (390/10,000 LB in 2010) (34) and China (780/10,000 LB in 2012) (35) . In this reading, it is important to think about the differences in the calculation of rates, since in none of the studies were accounted for fetal deaths, as indicated by the WHO and followed in this research.…”
Section: Discussionmentioning
confidence: 48%